Technology for facilitating humanity and combating social deviations : interdisciplinary perspectives - Vargas Martin, Miguel 1973; Garcia-Ruiz, Miguel A. 1970; Edwards, Arthur 1957 (Hershey, PA : Information Science Reference, 2011)
"This book presents socio-technical approaches to support the prevention, mitigation, and elimination of social deviations with the help of computer science and technology, providing historical backgrounds, experimental studies, and future perspectives on the use of computing tools to prevent and deal with physical, psychological and social problems that impact society as a whole"--Provided by publisher.
Includes index.
Bibliography: p. 287-312.
Keywords: Information technology -- Social aspects; Social problems